Extent of fibrosis and lung function decline in patients with systemic sclerosis and interstitial lung disease: data from the SENSCIS trial - Denton,CP; Goh,NS; Humphries,SM; Maher,TM; Spiera,R; Devaraj,A; Ho,L; Stock,C; Erhardt,E; Alves,M; Wells,AU; SENSCIS,trial investigators (Rheumatology, 2023)
OBJECTIVE: To assess associations between the extent of fibrotic interstitial lung disease (ILD) and forced vital capacity (FVC) at baseline and change in FVC over 52 weeks in patients with systemic sclerosis-associated ILD (SSc-ILD) in the SENSCIS trial. METHODS: We used generalised additive models, which involve few assumptions and allow for interaction between non-linear effects, to assess associations between the extent of fibrotic ILD on high-resolution computed tomography (HRCT), and the interplay of extent of fibrotic ILD on HRCT and FVC % predicted, at baseline and FVC decline over 52 weeks. RESULTS: In the placebo group (n = 288), there was weak evidence of a modest association between a greater extent of fibrotic ILD at baseline and a greater decline in FVC % predicted at week 52 (r: -0.09 [95% CI -0.2, 0.03]). Higher values of both the extent of fibrotic ILD and FVC % predicted at baseline tended to be associated with greater decline in FVC % predicted at week 52. In the nintedanib group (n = 288), there was no evidence of an association between the extent of fibrotic ILD at baseline and decline in FVC % predicted at week 52 (r: 0.01 [95% CI: -0.11, 0.12]) or between the interplay of extent of fibrotic ILD and FVC % predicted at baseline and decline in FVC % predicted at week 52. CONCLUSION: Data from the SENSCIS trial suggest that patients with SSc-ILD are at risk of ILD progression and benefit from nintedanib largely irrespective of their extent of fibrotic ILD at baseline. TRIAL REGISTRATION: ClinicalTrials.gov, https://clinicaltrials.gov, NCT02597933.